Parental Inflammatory Bowel Disease and Risk of Asthma in Offspring: A Nationwide Cohort Study in Denmark - Andersen, Ane Birgitte Telén (Nature Publishing Group, 2013)
OBJECTIVES: Common genetic and environmental risk factors may explain the concurrent increase in the incidence of both inflammatory bowel disease (IBD) and asthma. We examined whether IBD in a parent is associated with an increased asthma risk in offspring. METHODS: This was a registry-based cohort study of all children born alive in Denmark in 1979–2009, followed through 2010. IBD and asthma were identified using hospital diagnoses; antiasthma medication was also used to identify asthma. We computed risk of asthma and estimated adjusted incidence rate ratios (aIRRs) with 95% confidence intervals (CIs) using Cox proportional-hazards regression. We evaluated asthma risk according to maternal and paternal IBD, Crohn's disease (CD), and ulcerative colitis (UC). Children without parental IBD were the comparison cohort for all comparisons. RESULTS: We identified 1,845,281 children, of whom 14,952 (0.8%) had a parent with IBD. The 10-year risk of asthma was 6.9% among offspring of parents with CD, 5.6% among offspring of parents with UC, and 5.0% among offspring of parents without IBD. The aIRR for asthma associated with parental IBD was 0.98 (95% CI: 0.91–1.04). The aIRR was 1.09 (95% CI: 0.98–1.22) for parental CD and 0.92 (95% CI: 0.84–1.00) for parental UC. Results were similar regardless of parent of origin or inclusion of antiasthma medication to define asthma. CONCLUSIONS: Our data do not provide evidence for an increased risk of asthma in offspring with a parental history of IBD.